Asuhan Kebidanan Continuity Of Care (COC) Pada Ibu Hamil Anemia, Bersalin, Nifas, Bayi Baru Lahir Dan Keluarga Berencana Pada Ny. L Di Praktek Bidan E BR Manullang Kecamatan Habinsaran Kabupaten Toba Provinsi Sumatera Utara Tahun 2021 - Ginting, Fatmal Ekalia; Sihombing, Artha Tonggo Parsaulian; Sembiring, Netty Herawaty Br; Sapni, Nirmala; Nurhayati; Febriana Sari; Imarina Tarigan (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
The report from the Kab/City Profile of MMR reported in North Sumatra in 2014 was 75/100,000 live births, however, this cannot yet describe the actual MMR in the province. One of the efforts to improve the classification of midwives is to apply a model of sustainable midwifery care (Continuity Of Care / CoC) in clinical education. To provide comprehensive midwifery care with the application of varney midwifery management and SOAP Continuity of care (COC) midwifery care for pregnant women, maternity, postpartum, BBL, and family planning to Mrs "L" at the Independent Practice of Midwives Sumiati, Semadam District, Southeast Aceh Regency in 2021. Pregnancy examination on Mrs. L follows the 7T from the standard 10T. Mother was not tested for sexually transmitted diseases, and did not carry out case management. Normal delivery care at 37-40 weeks’ gestation at the time of delivery did not find any complications in the I, II, III and IV stages. Labor went normally without any complications or complications. Normal delivery care at 37-40 weeks’ gestation at the time of delivery did not find any complications in the I, II, III and IV stages. Labor went normally without any complications or complications. It is recommended that clinical leaders be able to apply continuity of care care to all patients who perform examinations for pregnancy, childbirth, the puerperium, newborns and family planning.